2006
DOI: 10.1007/s00426-006-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Do working-memory executive components mediate the effects of age on strategy selection or on strategy execution? Insights from arithmetic problem solving

Abstract: Younger and older adults performed an inequality verification task (7+6 < 15, Yes/No?) in a control condition and in a dual-task condition where they simultaneously performed an executive-component task. Arithmetic-problem characteristics were manipulated in order to test strategy selection (i.e., choice of appropriate strategies in order to improve performance) and strategy execution (i.e., performance of the cognitive processes involved in each strategy). Results revealed that strategy selection changes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Abstract code model (McCloskey, 1992); Triple-code model (Dehaene, 1992); Encoding complex model (Campbell & Clarke, 1992)], though some conceptual frameworks for mathematical development and disability do include this construct (e.g., Geary & Hoard, 2005). As such, these models may be missing an explanatory construct for understanding not only mathematical performance and individual differences but also the development and operation of mathematical skills across the life span (Duverne, Lemaire, & Vandierendonck, 2008;Hecht, 2002;LeFevre et al, 2005). From an applied perspective, knowing whether working memory is related to how children learn mathematics and why some children have difficulties in math may be important for instructional design.…”
mentioning
confidence: 95%
“…Abstract code model (McCloskey, 1992); Triple-code model (Dehaene, 1992); Encoding complex model (Campbell & Clarke, 1992)], though some conceptual frameworks for mathematical development and disability do include this construct (e.g., Geary & Hoard, 2005). As such, these models may be missing an explanatory construct for understanding not only mathematical performance and individual differences but also the development and operation of mathematical skills across the life span (Duverne, Lemaire, & Vandierendonck, 2008;Hecht, 2002;LeFevre et al, 2005). From an applied perspective, knowing whether working memory is related to how children learn mathematics and why some children have difficulties in math may be important for instructional design.…”
mentioning
confidence: 95%
“…Hence, these changes have been explicitly linked to declines in executive resources Duverne, Lemaire, & Vandierendonck, 2007;Rabinowitz, Craik, & Ackerman, 1982;Taconnat & Lemaire, in press), which are known to affect the elderly population (Salthouse, 1990). Reduced executive resources likely contribute to increased memory strategy switch costs in the elderly (Froger et al, 2012;Toczé et al, 2012) and even to a general reluctance to shifting strategies (Lemaire & Leclère, 2014).…”
mentioning
confidence: 98%
“…As shown in Figure 7, participants were slower under WM-load condition, and even more so for the harder, rounding-up strategy than for the simpler, rounding-down strategy. These two sets of findings revealed that executive functions of working memory are involved in arithmetic strategy use and strategy execution (see also Duverne, Lemaire, & Vandierendonck, 2008).…”
Section: Wm/ef and Arithmetic Problem Solvingmentioning
confidence: 82%